A single hybrid parameter-based model for calibrating hargreaves-samani coefficient in Nigeria - Nwokolo, Samuel; Ogbulezie, Julie (International Journal of Physical Research, 2017)
The present research was designed to locally calibrate Hargreaves-Samani computing model (HS) in twenty-one (21) locations with their corresponding coastal and interior regions in Nigeria employing a single hybrid parameter-based model to obtain the adjusted Hargreaves-Samani coefficient (AHC) for Nigerian environment. To achieve this purpose, meteorological parameters such as extraterrestrial solar radiation, maximum sunshine duration, minimum and maximum temperatures were employed as input parameters to compute the original HS model and equally calibrate the original HS model. The monthly AHCs were obtained by multiplying the 0.17 by the monthly ratio of the observed global solar radiation (H) to H calculated from original HS model. The average value was obtained per station. These observed AHC values were considered as the target values for the development of hybrid parameter-based models (HP) for every station used for calibrating original HS model. On the whole, the result from the statistical indicators confirmed that the locally calibrated HS model performed better than the original HS model in all stations (including coastal and interior regions) investigated. Both the original and calibrated HS models underestimated H at annual timescale, but the calibrated HS model provided closer average values with H, which could confirm the good performances of the calibrated HS model. Therefore, the calibrated HS model obtained in this research could be highly recommended for estimating H in Nigeria when only temperature data are available.